Organizational Culture, Religiosity, and Work Environment on Employee Performance at Yayasan Tunas Karya - Ganggali; Agustinus Priyowidodo (Komunitas Dosen Indonesia, 2025)
This study explores how organizational culture, religiosity, and the work environment, mediated by job satisfaction, influence employee performance. The research was conducted among employees of schools under the Yayasan Tunas Karya (YTK), foundation in the Bangka Belitung Province, Indonesia. This study used a quantitative method by gathering data from 171 respondents. The findings reveal that the organizational culture and the work environment both positively and significantly increase employees’ job satisfaction, which improves their overall performance as a whole. In contrast, religiosity does not have a noticeable impact on job satisfaction, but it directly contributes to performance by fostering ethical behaviour, discipline, and a sense of responsibility. The study also shows how job satisfaction is vital in connecting organizational culture and work environment with employee performance, emphasizing that satisfied employees are inclined to perform more effectively and contribute positively to their organizations. These findings demonstrate how crucial it is to build a supportive workplace culture, strengthening teamwork, and maintaining a healthy work environment to boost satisfaction and performance. At the same time, nurturing employees’ personal values and spirituality can further enhance their motivation and commitment.